Rees's manufacturing industry (1819-20) : - Rees, Abraham (David & Charles Reprints, 1972)
This volume covers eighty-one subjects from Forge to Molloses, and includes sections of plates illustrating Furnace, Iron Manufacture, Lamps, Lathe, Light House, Masonry, Mechanics, Mill Work, and Mineralogy. (See back panel for complete list of contents.)...